The Potential Implications of Hydrogen Sulfide in Aging and Age-Related Diseases through the Lens of Mitohormesis - Thi Thuy Tien Vo; Thao Duy Huynh; Ching-Shuen Wang; Kuei-Hung Lai; Zih-Chan Lin; Wei-Ning Lin; Yuh-Lien Chen; Tzu-Yu Peng; Ho-Cheng Wu; I-Ta Lee (MDPI AG, 2022)
The growing increases in the global life expectancy and the incidence of chronic diseases as a direct consequence have highlighted a demand to develop effective strategies for promoting the health of the aging population. Understanding conserved mechanisms of aging across species is believed helpful for the development of approaches to delay the progression of aging and the onset of age-related diseases. Mitochondrial hormesis (or mitohormesis), which can be defined as an evolutionary-based adaptive response to low-level stress, is emerging as a promising paradigm in the field of anti-aging. Depending on the severity of the perceived stress, there are varying levels of hormetic response existing in the mitochondria called mitochondrial stress response. Hydrogen sulfide (H2S) is a volatile, flammable, and toxic gas, with a characteristic odor of rotten eggs. However, H2S is now recognized an important gaseous signaling molecule to both physiology and pathophysiology in biological systems. Recent studies that elucidate the importance of H2S as a therapeutic molecule has suggested its protective effects beyond the traditional understanding of its antioxidant properties. H2S can also be crucial for the activation of mitochondrial stress response, postulating a potential mechanism for combating aging and age-related diseases. Therefore, this review focuses on highlighting the involvement of H2S and its sulfur-containing derivatives in the induction of mitochondrial stress response, suggesting a novel possibility of mitohormesis through which this gaseous signaling molecule may promote the healthspan and lifespan of an organism.